2001
DOI: 10.1038/sj.bjp.0703861
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of KCNQ5/Q3 potassium channels expressed in mammalian cells

Abstract: Heteromeric KCNQ5/Q3 channels were stably expressed in Chinese Hamster ovary cells and characterized using the whole cell voltage-clamp technique. KCNQ5/Q3 channels were activated by the novel anticonvulsant, retigabine (EC 50 1.4 mM) by a mechanism that involved drug-induced, leftward shifts in the voltage-dependence of channel activation (731.8 mV by 30 mM retigabine). KCNQ5/Q3 channels were inhibited by linopirdine (IC 50 7.7 mM) and barium (IC 50 0.46 mM), at concentrations similar to those required to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 16 publications
8
72
0
Order By: Relevance
“…Both linopirdine and XE991 evoked depolarization (Fig. 3, A and B), which could take several minutes to reach steady state and often showed only partial recovery over the time course of the experiments (Յ30 min), as found previously with recombinant KCNQ channels (Wickenden et al, 2001). Linopirdine depolarized cells by 9 mV (from Ϫ45 Ϯ 3 to Ϫ36 Ϯ 3 mV; n ϭ 8, p Ͻ 0.05) at 1 M and by 15 mV (from Ϫ48 Ϯ 3 to Ϫ33 Ϯ 7 mV; n ϭ 5, p Ͻ 0.05) at 10 M. Similar responses were seen with XE991 (Fig.…”
Section: Electrophysiological Effects Of Kcnq Channelmentioning
confidence: 71%
“…Both linopirdine and XE991 evoked depolarization (Fig. 3, A and B), which could take several minutes to reach steady state and often showed only partial recovery over the time course of the experiments (Յ30 min), as found previously with recombinant KCNQ channels (Wickenden et al, 2001). Linopirdine depolarized cells by 9 mV (from Ϫ45 Ϯ 3 to Ϫ36 Ϯ 3 mV; n ϭ 8, p Ͻ 0.05) at 1 M and by 15 mV (from Ϫ48 Ϯ 3 to Ϫ33 Ϯ 7 mV; n ϭ 5, p Ͻ 0.05) at 10 M. Similar responses were seen with XE991 (Fig.…”
Section: Electrophysiological Effects Of Kcnq Channelmentioning
confidence: 71%
“…Several classes of small-molecule activators for KCNQ channels have been identified and they differ in chemical structure, mode of action, and target selectivity (29)(30)(31)(32)(33)(34). For example, among five KCNQ channels, KCNQ1 to KCNQ5 (or Kv7.1-Kv7.5), Retigabine has a rank order of potency as KCNQ3 > KCNQ2 > KCNQ4 = KCNQ5 >> KCNQ1 according to the available data (34), whereas ZnPy has a rank order of efficacy as KCNQ4 >> KCNQ2 > KCNQ1 >> KCNQ3 (32).…”
Section: Discussionmentioning
confidence: 99%
“…The drug is therefore a "potassium channel opener." Subsequently, it was found that retigabine is specific for M-type potassium current, which is carried by KCNQ (Kv7)-type potassium channels (Rundfeldt and Netzer, 2000b;Main et al, 2000;Wickenden et al, 2001). M-current is a slowly activating current whose threshold is near resting potential.…”
Section: Retigabinementioning
confidence: 99%
“…There are four known neuronal KCNQ subunits (KCNQ2-5 or Kv7.2-7.5), which are homologous to KCNQ1 (KvLQT or Kv7.1), a cardiac potassium channel involved in one form of the long QT syndrome (Jentsch, 2000). Retigabine acts on all neuronal KCNQ subunits, but not on KCNQ1 which is expressed in cardiac muscle (Tatulian et al, 2001;Wickenden et al, 2001). Through the use of chimeras it has been possible to define elements of the KCNQ structure that are critical to the effects of retigabine on gating and presumably to its binding (Wuttke et al, 2005;Schenzer et al, 2005).…”
Section: Retigabinementioning
confidence: 99%